Examining the Mediating Role of Motivation in the Relationship between Multidimensional Perfectionism and Well- and Ill-Being in Vocational Dancers - Francisco L. Atienza (International Journal of Environmental Research and Public Health, 2020)
Perfectionism is considered to be an important personality factor within the dance context given the high number of dancers whose psychological health is influenced by its consequences. The relationship between perfectionism and dancers’ well- and ill-being can be mediated by a range of variables. The present study explores the role of forms of motivation (i.e., autonomous motivation, controlled motivation and amotivation) as mediators in the relationship between perfectionism (i.e., self-oriented and socially prescribed) and an indicator of well-being (i.e., subjective vitality) and ill-being (i.e., burnout). Participants of the study were 146 male and female Spanish vocational dancers aged between 12 and 26 years old (Mean age = 15.40 ± 2.96) who completed questionnaires measuring the variables of interest. Results of multiple mediator regression analyses showed that amotivation mediated the relationships between self-oriented and socially prescribed perfectionism with burnout and subjective vitality. Self-oriented perfectionism was negatively correlated, and socially prescribed perfectionism positively associated with amotivation. Amotivation of dancers was a positive predictor of burnout and a negative predictor of subjective vitality. Overall, the findings corroborate the importance of amotivation in the relationship between perfectionism dimensions and well-being and ill-being in dancers.